ANALISIS KOMPARATIF FAKTOR KEPUTUSAN PEMILIHAN DESTINASI WISATA ALAM PANTAI BENGKUNG VS GUNUNG PARALAYANG SAAT LIBUR LEBARAN - M Kurniawan Putra, Rivaldy, Taufik Mulyanto P, M Insan Romadhan (Integrative Perspectives of Social and Science Journal, 2025)
The Lebaran holiday period is one of the most significant times for Indonesians to travel, particularly to natural destinations. This study aims to compare the factors influencing tourists in choosing Pantai Bengkung in South Malang and Gunung Paralayang Batu as holiday destinations during the Lebaran season. Utilizing a qualitative approach through in-depth interviews and participatory observation, this research found that tourists visiting Pantai Bengkung are generally driven by the desire to seek tranquility and enjoy the ocean scenery, whereas visitors to Gunung Paralayang Batu are more motivated by the unique experiences and opportunities to create content for social media. These findings can serve as a reference for destination managers in formulating promotional strategies that align with the interests and preferences of tourists.